The Permanence of Temporary Urbanism : Normalising Precarity in Austerity London - Ferreri, Mara (Book collections on Project MUSE., 2021)
Temporary urbanism has become an established marker of city making after the 2008 Global Financial Crisis. The book offers a critical exploration of its emergence and establishment as a seductive discourse and as an entangled field of urban practice encompassing architecture, visual and performative arts, urban regeneration and planning. Drawing on seven years of semi-ethnographic research in London, it explores the politics of temporariness at time of austerity from a situated analysis of neighbourhood transformation and wider cultural and economic shifts. Through a sympathetic, longitudinal engagement with projects and practitioners, the book tests the power of aesthetic and cultural interventions and highlights tensions between the promise of practices of dissenting vacant space re-appropriation, and their practical foreclosure. Against the normalisation of ephemerality, it develops a critique of temporary urbanism as a glamorisation of the anticipatory politics of precarity, transforming subjectivities and imaginaries of urban action. Bron: Flaptekst, uitgeversinformatie.